PENGUKURAN KELELAHAN KERJA DAN EVALUASI POSTUR KERJA PADA PEKERJA PELONGGARAN GARAM - Basri, Moh. Subhan; Satoto, Handy Febri (Universitas Majalengka, 2024)
This study aims to measure the physical workload experienced by workers in Pegaraman 1 Sumenep, PT Garam (Persero). With a production of 115,000 tons per season, Pegaraman Area 1 Sumenep faces a huge challenge in achieving production targets with the use of efficient tools for workers. This is the problem that causes work fatigue, based on the identification of the research conducted. To overcome this problem, the research will focus on measuring the physical workload of salt loosening workers using the NBM, REBA, and CVL methods, in the hope of finding the right solution to solve problems related to work fatigue during the salt loosening process. The results showed that workers experienced physical workloads that needed action, with the results of the NBM recapitulation with a value of 50–70 risk levels, the REBA score with a value of 4, and CVL percentage values of 54.53% for the first worker, 55.21% for the second worker, and 53.67% for the third worker. Based on these findings, it can be concluded that the use of simple tools causes fatigue in workers. Therefore, an innovation is needed in the design of salt loosening tools to reduce the risk of fatigue in workers.